2022
DOI: 10.1097/jcp.0000000000001627
|View full text |Cite
|
Sign up to set email alerts
|

Combination of Long-Acting Injectable Antipsychotics in the Treatment of Psychiatric Disorders—A Systematic Review of the Literature and Case Series

Abstract: BackgroundThe treatment of refractory schizophrenia is complex, and compliance with oral treatment, including clozapine, can be challenging at times. The purpose of this case series and literature review article is to evaluate the efficacy of the combined use of 2 different long-acting injectable antipsychotics (LAIAs) on the number of psychiatric hospitalizations and emergency department visits. There are currently few data to support this treatment option, despite the frequent use of combinations of oral ant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(18 citation statements)
references
References 21 publications
(85 reference statements)
0
0
0
Order By: Relevance
“…A total of 15 studies was included in this review. Of these, nine were case reports [84,[86][87][88][89][90][96][97][98], four case series [85,[99][100][101], and two were observational retrospective studies [94,95]. No randomized clinical trial has been found that met the inclusion criteria.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…A total of 15 studies was included in this review. Of these, nine were case reports [84,[86][87][88][89][90][96][97][98], four case series [85,[99][100][101], and two were observational retrospective studies [94,95]. No randomized clinical trial has been found that met the inclusion criteria.…”
Section: Resultsmentioning
confidence: 99%
“…Of these, 29 (23.57%) were male and 11 (8.94%) female; no data about gender were available for the remaining 94 subjects (63.48%), who were all included in one study [95]. The sample's age ranged from 16- [101] to 67- [85] years-of-age. All patients received a diagnosis of schizophrenia (N = 68) [84][85][86][87]89,[94][95][96][97][98][99][100][101] or schizoaffective disorder (N = 43) [85,88,90,94,95], with the exception of 12 patients, whose main diagnosis was represented by bipolar disorder (N = 6), organic diseases (N = 2), and intellectual disability (N = 4) [95].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations